Ambagan 2013 mga salita mula sa iba't ibang wika sa Filipinas - Coroza, Michael M.; Pambansang Kumperensiyang Ambagan 2013 Ateneo de Manila University). (Quezon City The University of the Philippines Press, 2015)
On dialects of regions in the Philippines; papers of a conference.
Keywords: Philippine language -- Dialects -- Glossaries, vocabularies, etc; Philippine languages -- History -- Congresses; Philippines -- Languages